Cancer statistics, 2014. (7th January 2014) - Siegel, Rebecca; Ma, Jiemin; Zou, Zhaohui; Jemal, Ahmedin
Abstract Each year, the American Cancer Society estimates the numbers of new cancer cases and deaths that will occur in the United States in the current year and compiles the most recent data on cancer incidence, mortality, and survival. Incidence data were collected by the National Cancer Institute, the Centers for Disease Control and Prevention, and the North American Association of Central Cancer Registries and mortality data were collected by the National Center for Health Statistics. A total of 1, 665, 540 new cancer cases and 585, 720 cancer deaths are projected to occur in the United States in 2014. During the most recent 5 years for which there are data (2006‐2010), delay‐adjusted cancer incidence rates declined slightly in men (by 0.6% per year) and were stable in women, while cancer death rates decreased by 1.8% per year in men and by 1.4% per year in women. The combined cancer death rate (deaths per 100, 000 population) has been continuously declining for 2 decades, from a peak of 215.1 in 1991 to 171.8 in 2010. This 20% decline translates to the avoidance of approximately 1, 340, 400 cancer deaths (952, 700 among men and 387, 700 among women) during this time period. The magnitude of the decline in cancer death rates from 1991 to 2010 varies substantially by age, race, and sex, ranging from no decline among white women aged 80 years and older to a 55% decline among black men aged 40 years to 49 years. Notably, black men experienced the largest drop within every 10‐year age group. Further progress can be accelerated by applying existing cancer control knowledge across all segments of the population. CA Cancer J Clin 2014;64:9–29.© 2014 American Cancer Society, Inc.